2021
DOI: 10.1111/ijcp.14360
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of phytoestrogens in the treatment of perimenopausal and postmenopausal depressive disorders: A systematic review and meta‐analysis

Abstract: Background: Depression is one of the most common and specific symptoms among menopausal women, leading to significant personal, family, and economic burdens. Some studies have shown that phytoestrogens can help relieve symptoms of depression.Objectives:This systematic review and meta-analysis aim to assess the efficacy and safety of phytoestrogens in treating depression among menopausal women. Methods: A comprehensive search for relevant studies published until November 25, 2020, was conducted in PubMed, the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Based on a recent meta-analysis study, low-dose isofavone (dose <100 mg/day) has a safety profle without any serious side efects. Only minimal adverse effects such as abdominal pain, diarrhea, myalgia, and headache have been reported [33]. Te limitations of this trial include the short period of intervention, relatively small sample size, and single-center design.…”
Section: Discussionmentioning
confidence: 97%
“…Based on a recent meta-analysis study, low-dose isofavone (dose <100 mg/day) has a safety profle without any serious side efects. Only minimal adverse effects such as abdominal pain, diarrhea, myalgia, and headache have been reported [33]. Te limitations of this trial include the short period of intervention, relatively small sample size, and single-center design.…”
Section: Discussionmentioning
confidence: 97%
“…A meta‐analysis including 10 RCTs ( n = 1248) found that phytoestrogens significantly reduced depressive symptoms in postmenopausal women relative to control (Li, Li, et al, 2021), with isoflavones reported as more effective (Standardised Mean Difference [SMD] = −0.48; 95% CI: −0.75, 0.21) than lignans (SMD = −0.22; 95% CI: −0.37, 0.08). However, no significant difference in symptoms was reported among perimenopausal women (Li, Guo, et al, 2021).…”
Section: Symptoms Of the Menopausementioning
confidence: 99%
“…Although low levels of vitamin B12 have been associated with lower cognitive performance (Lambrinoudaki et al, 2013), studies exploring the relationship between vitamin B12 supplementation and cognitive decline have tended to focus on the ageing process rather than the menopausal transition (Ford & Almeida, 2019; Li, Li, et al, 2021; Markun et al, 2021; Wang et al, 2021). Therefore, the potential benefits of B vitamin supplementation during the menopausal transition remain unclear.…”
Section: Symptoms Of the Menopausementioning
confidence: 99%
“…Phytoestrogens have been extensively studied for their potential role to prevent and treat diseases related to aging such as menopausal symptoms and skin aging, cardiovascular, neurodegenerative, immune and metabolic diseases and cancer. Recent systematic review and meta-analysis reported that consumption of low doses of phytoestrogen (25 mg/d ≤ dose ≤100 mg/d) for a long-term duration were effective in relieving depression symptoms in postmenopausal women (Li et al, 2021). Some reported adverse effect associated to phytoestrogens in menopausal women however are not yet clear and required more supportive evidence from high-quality randomized control trial (RCT) studies.…”
Section: Therapeutic Potential Of Phytoestrogensmentioning
confidence: 99%